Analisis Efektivitas Pemungutan Pajak Reklame di Masa Pandemi Covid-19 Pada Badan Pendapatan Daerah Kabupaten Langkat - Zulia Hanum (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2021)
The aim is to analyze the Effectiveness of Collecting Advertising Taxes During the Covid-19 Period at the Regional Revenue Agency of the Regency. Langkat. This study used qualitative research methods. This research uses documentation data sources and interviews with 1 resource person. Data collection techniques used in the form of observation, interviews, and documentation. The data analysis technique used in this research is descriptive analysis with qualitative data. The results of this study indicate that: (1) The results of the effectiveness analysis show that during the Covid-19 pandemic that occurred in 2020, it decreased to 45.26% which means that the billing tax collection is not effective at the District Revenue Agency. Langkat. (2) Efforts that can be made to overcome the decline in advertising tax revenue in Kab. Langkat in 2020 due to the Covid-19 pandemic, namely: As a form of providing assistance and relief from advertising tax payments.